2021
DOI: 10.1101/2021.11.21.469455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signaling by the integrated stress response kinase PKR is fine-tuned by dynamic clustering

Abstract: The double-stranded RNA sensor kinase PKR is one of four integrated stress response (ISR) sensor kinases that phosphorylate the alpha subunit of the eukaryotic initiation factor 2 (eIF2α) in response to stress. The current model of PKR activation considers the formation of back-to-back PKR dimers as a prerequisite for signal propagation. Here we show that PKR signaling involves the assembly of dynamic PKR clusters. PKR clustering is driven by ligand binding to PKR’s sensor domain and by front-to-front interfac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…5H) Thus, A3B has a critical function in regulating PKR during infection with different types of RNA viruses. Finally, we asked whether A3B impacts PKR-dsRNA condensates that are formed when dsRNAs are present in the cytoplasm 80,81 . We transfected cells with poly(I:C)-FITC to monitor PKR colocalization with dsRNAs and we confirmed that PKR formed large foci that are associated with poly(I:C) (Supplementary Fig.…”
Section: Apobec3b Promotes Pkr Activity During Viral Infectionmentioning
confidence: 99%
“…5H) Thus, A3B has a critical function in regulating PKR during infection with different types of RNA viruses. Finally, we asked whether A3B impacts PKR-dsRNA condensates that are formed when dsRNAs are present in the cytoplasm 80,81 . We transfected cells with poly(I:C)-FITC to monitor PKR colocalization with dsRNAs and we confirmed that PKR formed large foci that are associated with poly(I:C) (Supplementary Fig.…”
Section: Apobec3b Promotes Pkr Activity During Viral Infectionmentioning
confidence: 99%
“…We chose to engineer optogenetic control over PKR for two reasons. First, PKR's activation mechanism involves high-order self-association (Corbet et al, 2022;Mayo et al, 2019;Zappa et al, 2021), which can be mimicked using optogenetic clustering tools. Second, PKR is cytoplasmically localized and its sensor domain is isolated to a contiguous stretch of amino acids on the polypeptide chain, making it easier to engineer in comparison to the other ISR kinases (Cole, 2007;Zhu et al, 1997).…”
Section: Optogenetic Activation Of Pkr Induces the Isrmentioning
confidence: 99%
“…ISRIB (Sigma-Aldrich), 50 µM Z-VAD-FMK (SelleckChem), or 1 µg/ml FcDR5 (R&D systems) as indicated. FKBP-PKR was activated with 100 nM of the homodimerization ligand AP20187 (Takara), as previously described (Zappa et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Pseudoclonal cell populations were obtained by fluorescence-activated cell sorting using a narrow gate placed over the mean of the signal distribution as previously described (Zappa et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation